Advancements in Information-Theoretic Methods for Data Analytics - Kichun Lee (Entropy)
A defining feature of the current epoch is a historically unparalleled increase in information, data that originates from a wide spectrum of scientific disciplines, industrial processes, and societal interactions [...]